Lignin from sugar cane bagasse: Extraction, fabrication of nanostructured films, and application - Pereira, A. A.; Martins, G. F.; Antunes, P. A.; Conrrado, R.; Pasquini, D.; Job, A. E.; Curvelo, A. A. S.; Ferreira, M.; Riul, A.; Constantino, C. J. L. (Amer Chemical Soc, 2007)
Four lignin samples were extracted from sugar cane bagasse using four different alcohols (methanol, ethanol, n-propanol, and 1-butanol) via the organosolv-CO2 supercritical pulping process. Langmuir films were characterized by surface pressure vs mean molecular area (Pi-A) isotherms to exploit information at the molecular level carrying out stability tests, cycles of compression/expansion (hysteresis), subphase temperature variations, and metallic ions dissolved into the water subphase at different concentrations. Briefly, it was observed that these lignins are relatively stable on the water surface when compared to those obtained via different extraction processes. Besides, the Pi-A isotherms are shifted to smaller molecular areas at higher subphase temperatures and to larger molecular areas when the metallic ions are dissolved into the subphase. The results are related to the formation of stable aggregates (domains) onto the water subphase by these lignins, as shown in the Pi-A isotherms. It was found as well that the most stable lignin monolayer onto the water subphase is that extracted with 1-butanol. Homogeneous Langmuir-Blodgett (LB) films of this lignin could be produced as confirmed by UV-vis absorption spectroscopy and the cumulative transfer parameter. In addition, FTIR analysis showed that this lignin LB film is structured in a way that the phenyl groups are organized preferentially parallel to the substrate surface. Further, these LB films were deposited onto gold interdigitated electrodes and ITO and applied in studies involving the detection of Cd+2 ions in aqueous solutions at low concentration levels throughimpedance spectroscopy and electrochemical measurements. FTIR spectroscopy was carried out before and after soaking the thin films into Cd+2 aqueous solutions, revealing a possible physical interaction between the lignin phenyl groups and the heavy metal ions. The importance of using nanostructured systems is demonstrated as well by comparing both LB and cast films.